The Agricultural Insurance: Explore Trends and Advances Over the Last Two Decades - ADRIANI, IKA RESKIANA; Ekasasmita, Wahyuni; Afriansyah, Dilla; Zahra, Khoiruz (FKIP Universitas Mataram, 2025)
The agricultural sector faces major risks due to extreme climate change, market uncertainty and economic fluctuations, which can destabilize global food production. Agricultural insurance, despite its importance as a risk mitigation tool for farmers, still has limited article reviews compared to other insurance sectors such as health, life, and property. This study aims to conduct a bibliometric analysis of global research on agricultural insurance over the past two decades, focusing on publication trends, the most influential countries and journals, keyword analysis, and providing directions for future research. The study used data from Scopus with a total of 643 documents. Analysis was conducted using VOS viewer, RStudio, and Tableau to visualize collaboration patterns, dominant keywords, and global publication trends. The analysis shows a significant increase in the number of studies on agricultural insurance, which reinforces the urgency of insurance in supporting global food stability. The implications of this research point to the need to develop insurance models that are technology-based and more adaptive to climate change, especially to expand access for smallholder farmers in developing countries. Recommendations for future research are to strengthen cross-sector collaboration and technological innovation to support the sustainability and resilience of the agricultural sector in the future.